2018
DOI: 10.15414/raae.2018.21.01.40-54
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Foreign Direct Investment (Fdi) on Agricultural Growth in Nigeria (1979-2014)

Abstract: This study examining the impact of foreign direct investment (FDI) and other macroeconomic variables on agricultural growth in Nigeria from 1981 to 2014, using annual time series data from Central Bank of Nigeria (CBN), World Bank and the United States of America (US) Federal Reserve System. Data was analysed using trend analyses, unit root tests, co-integration tests, ordinary least squares (OLS) regression and Granger causality tests, while the hypothesis was tested with F-test. Results revealed very low FDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Additionally, there appears to be no multicollinearity or heteroskedasticity issues in the data. Hence, these results are in line with and consistent with some earlier investigations, including (Owutuamor & Arene, 2018).…”
Section: Conclusion and Discussionsupporting
confidence: 94%
“…Additionally, there appears to be no multicollinearity or heteroskedasticity issues in the data. Hence, these results are in line with and consistent with some earlier investigations, including (Owutuamor & Arene, 2018).…”
Section: Conclusion and Discussionsupporting
confidence: 94%
“…Alfaro found that agricultural FDI had a negative effect on agricultural production efficiency by using the data of OECD countries [26]. Owutuamor et al used the Ordinary Least Square (OLS) and Granger Causality Test to study the impact of FDI on agricultural growth in Nigeria, and found that agricultural FDI had a certain inhibitory effect on agricultural growth [27]. Meng and Li adopted the Data Envelopment Analysis (DEA) method to study the relationship between agricultural FDI and agricultural TFP in 15 provinces in China from 2000 to 2011, and found that agricultural FDI had a significant negative impact on agricultural TFP, and had no obvious promoting effect on technical progress [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the one hand, the host government needs to guide investment. Some scholars believe that poor land governance and weak institutional capacity in developing countries make many investment projects economically, socially or environmentally unsustainable [65,66]. Therefore, optimizing investment effect requires strengthening land management and institutional development, and increasing public investment to increase smallholder productivity [67].…”
Section: Policy Implicationsmentioning
confidence: 99%